Morphological approach to extract ridge and valley connectivity networks from Digital Elevation Models - Sagar, B. S. Daya; Murthy, M. B. R.; Rao, C. Babu; Raj, Baldev (2003)
The extraction of ridge and valley connectivity networks is essential for studying spatio-temporal organizations. Extraction of such connectivity networks from multiscale DEMs has lately received notable attention. A simple method is proposed to extract these networks, from a sample DEM as well as a simulated fractal DEM, using non-linear morphological transformations in a methodical way. Further, the proposed method can be adapted to extract these complex topological networks from DEMs generated from either remotely sensed or topographic data.